UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN BUTIR SOAL MELALUI FOCUS GROUP DISCUSSION (FGD) DI SD NEGERI 173110 HUTARAJA - RESTI PASARIBU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve the ability of teachers to compile items through focus group discussions (FGD) at SD Negeri 173110 Hutaraja, Tarutung District, North Tapanuli Regency. The benefit of this research for schools and teachers is to have teachers who are skilled in compiling items. The research was conducted using the school action research method, which consisted of two cycles. The steps in each cycle consist of planning (planning), action (acting), observation (observing), and reflection (reflecting). The technique of collecting data is through observation by using an assessment scale tool (check list) to observe the discussion process about the teacher's ability to arrange items. Data validation in this school action research (PTS) uses member check, triangulation, and audit trail. How to analyze the data using descriptive qualitative analysis based on the results of observations and reflections. The results obtained prove that with the implementation of focus group discussions (FGD) in compiling items there is an increase in teacher ability assessed from the observation of activities in discussion activities using 48.75 in the LESS criteria, to 69.58 in the ENOUGH criteria and in the last cycle to 89 ,17 in GOOD criteria. These results prove that they have met the success criteria, namely at least getting a score in the range of 70-89 and included in the GOOD criteria. These results prove that they have met the success criteria, namely at least getting a score in the range of 70-89 and included in the GOOD criteria, and the observation of the ability to compose items using 18 indicators proves an increase in each cycle from the initial condition of 50.00 in the LESS criteria with an explanation of 68, 52 in the ENOUGH criteria and in the last cycle to 88.89 in the GOOD criteria. These results prove that they have met the success criteria, namely at least getting a score in the range of 70-89 and included in the GOOD criteria. These results prove that they have met the success criteria, namely at least getting a score in the range of 70-89 and included in the GOOD criteria. The conclusion is that the implementation of focus group discussions (FGD) at SD Negeri 173110 Hutaraja, Tarutung District, North Tapanuli Regency was proven to be able to improve the ability of teachers in preparing questions. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan guru menyusun butir soal melalui focus group discussion (FGD) di SD Negeri 173110 Hutaraja Kecamatan Tarutung Kabupaten Tapanuli Utara. Manfaat dari penelitian ini bagi sekolah dan guru adalah mempunyai guru yang terampil dalam menyusun butir soal. Penelitian dilakukan dengan menggunakan metode penelitian tindakan sekolah, yang terdiri dari dua siklus. Langkah-langkah dalam setiap siklus terdiri dari perencanaan (planning), tindakan (acting), obervasi (observing), dan refleksi (reflecting). Teknik pengumpulan data melalui observasi dengan menggunakan alat skala penilaian (check list) untuk mengamati proses diskusi tentang kemampuan guru menyusun butir soal. Validasi data dalam penelitian tindakan sekolah (PTS) ini menggunakan member check, triangulasi, dan audit trail. Cara menganalisis data menggunakan analisis deskriptif kualitatif berdasarkan hasil observasi dan refleksi. Hasil yang diperoleh membuktikan bahwa dengan pelaksanaan focus group discussion (FGD) dalam menyusun butir soal terjadi kenaikan kemampuan guru dinilai dari observasi aktivitas pada kegiatan diskusi dengan menggunakan 48,75 dalam kriteria KURANG, menjadi 69,58 dalam kriteria CUKUP serta pada siklus terakhir menjadi 89,17 dalam kriteria BAIK. Hasil tersebut membuktikan telah memenuhi kriteria keberhasilan yaitu minimal mendapat nilai dalam rentang 70-89 dan masuk dalam kriteria BAIK. Hasil tersebut membuktikan telah memenuhi kriteria keberhasilan yaitu minimal mendapat nilai dalam rentang 70-89 dan masuk dalam kriteria BAIK, dan observasi kemampuan menyusun butir soal dengan menggunakan 18 indikator membuktikan peningkatan pada setiap siklusnya dari kondisi awal sebesar 50.00 dalam kriteria KURANG dengan penjelasan menjadi 68,52 dalam kriteria CUKUP serta pada siklus terakhir menjadi 88,89 dalam kriteria BAIK. Hasil tersebut membuktikan telah memenuhi kriteria keberhasilan yaitu minimal mendapat nilai dalam rentang 70-89 dan masuk dalam kriteria BAIK. Hasil tersebut membuktikan telah memenuhi kriteria keberhasilan yaitu minimal mendapat nilai dalam rentang 70-89 dan masuk dalam kriteria BAIK. Kesimpulannya adalah pelaksanaan focus group discussion (FGD) di SD Negeri 173110 Hutaraja Kecamatan Tarutung Kabupaten Tapanuli Utara terbukti mampu meningkatkan kemampuan guru dalam menyusun butir soal.